The influence of retrograde cerebral perfusion on retinal microcirculation in type A aortic dissection surgery - (:unkn) unknown (BAYCINAR MEDICAL PUBL-BAYCINAR TIBBI YAYINCILIK, 2009)
Background The aim of this study was to evaluate the influence of retrograde cerebral perfusion on retinal microcirculation in patients operated on for aortic dissections. Methods: Thirty patients underwent surgery for aortic dissections. Of these, 15 patients underwent replacement of the ascending aorta alone (group 1; 12 mates, 3 females; mean age 45 +/- 16 years; range 29 to 64 years), and 15 patients underwent replacement of the ascending aorta and aortic arch (group 2; 10 males, 5 females; mean age 49 +/- 12 years; range 33 to 65 years). The intimal tear was resected and the ascending aorta and aortic arch were replaced with a woven collagen-impregnated Dacron graft. Additional procedures in group 1 included aortic root replacement with the flanged technique in four patients and coronary bypass grafting in one patient. In group 2, nine patients had hemiarcus, six patients had total arcus replacement depending on the location of the intimal tear. The elephant trunk procedure was used in 10 patients. Fundus examinations were performed in the first postoperative 24 to 48 hours and four weeks after the operation. Results: Ocular complications were detected in 12 patients (4 in group 1, and 8 in group 2). Blurred vision was found in nine patients and retinal paleness in three patients. Binocular photopsia persisted in three patients (all in group 2) after four postoperative weeks. The incidence of transient ocular dysfunction was significantly higher in group 2 (p<0.05). Conclusion: Binocular ischemic retinopathy can be a sign of the effectiveness of cerebral protection during aortic dissection surgery. Therefore, ophthalmic examination can be a useful method of observing cerebral perfusion directly during dissection surgery.
Keywords: Aneurysm, dissecting/surgery; aortic aneurysm, thoracic/surgery; brain/blood supply; cerebrovascular circulation; microcirculation; perfusion/methods; retinal artery/blood supply; ARCH REPLACEMENT